The Influence of Price and Product Quality on Consumer Decisions to Purchase Jamblang Rice - Achmad Faqih; Siti Aisyah; Afif Agung Nugroho; Muhammad Adi Pratama; Reni Rismayanti; Abinaya Rafi Maulana (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
This study aims to find out: (1) The effect of price on consumer decisions to purchase jamblang rice, (2) The influence of product quality on consumer decisions to purchase jamblang rice (3) The influence between price and product quality on consumer decisions to purchase jamblang rice, using questionnaires as a tool to find out information from respondents with a total of 100 respondents. The research was conducted in May – July 2022. The data used are primary data and secondary data. The analysis methods used are classical assumption test analysis, multiple linear regression, f test analysis, t test analysis, and determination test analysis. The results showed that: (1) price variables affect consumer decisions to purchase jamblang rice around the Pasalaran Market of Weru Lor Village by obtaining a calculated value of 7,616 > table 1,984 using a significant limit of ? = 0.05%, (2) product quality affects consumer decisions to purchase jamblang rice obtained a calculated value of 3,521 > table 1,984 using a significant limit of ? = 0.05 %. (3) Price and product quality variables affect consumer decisions to purchase jamblang rice with the results of the analysis shown multiple regression equations as follows: Y = -6.648 + 0.769 X1 + 0.362 X2. This proves that the price variable has a greater influence on purchasing decisions compared to the product quality variable